Finitely bi-quasieegular Relations - Vinčić, Milovan; Romano, Daniel A. (Sarajevo Journal of Mathematics, 2024)
In this paper, analogously to the study of finitely regular (conjugative, dually normal and quasi-conjugative) relations, finitely bi-quasiregular relations are introduced and investigated. More concretely, after some preparations, an intrinsic characterization of such relations is established.